Genetic Variability and Evolutionary Dynamics of Papaya Ringspot Virus and Papaya Leaf Distortion Mosaic Virus Infecting Feral Papaya in Hainan Island - Yang, Mu-Zhi; Hao, Zhi-Gang; Ren, Zhen-Tao; Tang, Rui; Wu, Qing-Hua; Zhou, Li-Ying; Hu, Yu-Juan; Guo, Jing-Yuan; Chen, Yi; Guo, Yun-Ling; Liu, Biao; Liu, Lai-Pan; et al. (Phytopathology, 2024)
Commercialized genetically modified (GM) papaya cultivars have protected papaya from the devastating disease caused by papaya ringspot virus (PRSV). However, papaya leaf distortion mosaic virus (PLDMV), which causes similar infection symptoms but is serologically distinct from PRSV, was found to be a competitive threat to the papaya industry. Our study surveyed the occurrence of PRSV and PLDMV, as well as the transgenic markers of the 35S promoter from cauliflower mosaic virus and the neomycin phosphotransferase II gene in feral papaya plants, which were found frequently growing outside of cultivated papaya fields on Hainan Island. In total, 123 feral papayas, comprising 62 (50.4%) GM plants and 61 (49.6%) non-GM ones, were sampled. Among them, 23 (18.7%) were positive for PRSV, 49 (39.8%) were positive for PLDMV (including five plants co-infected by PRSV and PLDMV), and 56 (45.5%) were free of either virus. In traditional papaya-growing regions, we detected fewer PRSV-infected plants (2 in 33, 6%) than in other regions (21 in 90, 23%). However, overall, whether plants were transgenic or not made no difference to PRSV incidence ( = 0.230), with 9 PRSV-infected plants among 62 GM papayas and 14 among 61 non-GM papayas. Phylogenetic and genetic differentiation analysis showed a clear correlation between PRSV and PLDMV populations and their geographic origins. Negative selection was estimated for the selected gene regions of both viruses. Notably, PLDMV has deviated from neutral evolution and experienced population expansion, exhibiting increased genetic diversity, and is becoming the predominant threat to papaya in Hainan.